2004
DOI: 10.1530/rep.1.00240
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria in human oogenesis and preimplantation embryogenesis: engines of metabolism, ionic regulation and developmental competence

Abstract: Mitochondria are the most abundant organelles in the mammalian oocyte and early embryo. While their role in ATP production has long been known, only recently has their contribution to oocyte and embryo competence been investigated in the human. This review considers whether such factors as mitochondrial complement size, mitochondrial DNA copy numbers and defects, levels of respiration, and stage-specific spatial distribution, influence the developmental normality and viability of human oocytes and preimplantat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
201
0
8

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 311 publications
(234 citation statements)
references
References 89 publications
11
201
0
8
Order By: Relevance
“…Therefore, these data suggest that mitochondrial activity is a determinant factor of quality and changes in mitochondrial activity can alter oocyte quality in a remarkable way. In cattle (Tarazona et al 2006), horses , humans (Van Blerkom 2004) and pigs (Torner et al 2004) an increase in mitochondrial activity after IVM was described. In cattle, Torner et al (2008) observed higher mitochondrial activity in BCBK oocytes than in BCBC.…”
Section: Discussionmentioning
confidence: 98%
“…Therefore, these data suggest that mitochondrial activity is a determinant factor of quality and changes in mitochondrial activity can alter oocyte quality in a remarkable way. In cattle (Tarazona et al 2006), horses , humans (Van Blerkom 2004) and pigs (Torner et al 2004) an increase in mitochondrial activity after IVM was described. In cattle, Torner et al (2008) observed higher mitochondrial activity in BCBK oocytes than in BCBC.…”
Section: Discussionmentioning
confidence: 98%
“…Such mitochondrial dysfunction affecting ATP production during development may result in empty sacs and other features of fetal loss. Thus , it is possible that some mtDNA mutations cause a developmental arrest before pregnancy is clinically recognized [45].…”
Section: Discussionmentioning
confidence: 99%
“…These are mostly observed either to one side of the cytoplasm or in the centre. Oocyte granularity is correlated with the localisation of mitochondria and may represent domains of high ATP request that are necessary for the normal development of embryos [52,53]. However, granularity focused in the centre of the oocyte is considered a dysmorphism [50].…”
Section: Methodsmentioning
confidence: 99%